Chapter 16 Same-gender friendships and enmity in the Life of Eupraxia - Constantinou, Stavroula (Taylor & Francis, 2022)
Byzantine Literature, Literature, Byzantine History, History, Poetry, Greek Literature, Byzantine Culture, Late Antique Literature, Medieval Literature, Classical Literature, and Hagiography